Foreign Financial Flows on Financial Efficiency in Sub-Sahara African Countries - Ibrahim, Rahji Ohize; Nageri, Kamaldeen Ibrahem (Copernican Journal of Finance & Accounting, 2024)
The level of financial efficiency in Sub-Saharan Africa (SSA) remained low and incomparable to that of industrialized nations of the world, despite the supposed advantages of foreign capital inflows. This study examined the relationship between foreign financial inflows and financial efficiency in Sub-Saharan Africa against this backdrop (SSA). This study’s specific goals are to look into how remittance inflows affected financial efficiency in SSA and how FDI inflows affected it as well. Out of 49 countries in Sub-Saharan Africa, 42 were chosen for the study using a purposive sampling technique and an ex-post facto research design. The study used pooled mean group, mean group, and dynamic fixed effects techniques to estimate the model parameters using panel autoregressive distributed lag (PARDL) methods of estimation. The findings revealed that remittance inflows have significant positive impact on the financial efficiency, while FDI inflows have insignificant influence on the financial efficiency. In addition, the combination of economic growth with remittance inflows yielded negative impact on the financial efficiency while the combination of economic growth with FDI inflows yielded a positive impact on financial efficiency. The study concluded that remittance and FDI inflows play vital roles in guaranteeing improvement in financial efficiency of Sub-Sahara African countries directly and indirectly through inclusive economic growth. The study recommended that financial openness policies, like removing restrictions and encouraging free flow of financial resources between entities in domestic economy and foreign economies to promote further foreign financial inflows and enhance further financial efficiency. It is also recommended that financial openness policy should be pursued alongside inclusive economic growth measures such as economic diversification policies.